Hydrophobic Modification of Chitosan and its Physicochemical Evaluation as Sustained Release Tablet Formulation - Singh*, V.; Tiwari, M. (Asian Journal of Chemistry, 2011)
Chitosan is being investigated widely for use as an excipient in oral and other pharmaceutical formulations. Chitosan is generally regarded as a nontoxic and non-irritant material. It is biocompatible with both healthy and infected skin. Chitosan has been shown to be biodegradable (LD50 (mouse, oral): > 16 g/kg). Unmodified chitosan exhibited a low degree of disorder and a weak tablet crushing strength. In the present work, the hydrophobically modified chitosan were synthesized in order to formulate a system for sustain release of hydrophilic drug (indomethacine prototype drug in present case). The caproyl (C-8), decanoyl (C-10), lauryl (C-12), myristyl (C-14), palmitoyl (C-16) and stearoyl (C-18), fatty acyl derivatives of chitosan were prepared and physicochemically evaluated as excipient in matrix tablet dosage. The best sustained release studies was defined by palmitoyl chitosan and it can able sustain 50-60 % release upto 12 h and in concentration range 10-30 % much less as compared to chitosan (> 50 %).